miR-377-3p-Mediated EGR1 Downregulation Promotes B[a]P-Induced Lung Tumorigenesis by Wnt/Beta-Catenin Transduction - Ke, Xinxin; He, Lulu; Wang, Runan; Shen, Jing; Wang, Zhengyang; Shen, Yifei; Fan, Longjiang; Shao, Jimin; Qi, Hongyan (Frontiers in Oncology, 2021)
Polycyclic aromatic hydrocarbons (PAHs), particularly Benzo[a]pyrene (B[a]P), contained in cigarette smoke and air pollution, belong to a category of important carcinogens for lung cancer. However, early molecular events and related regulatory effects of B[a]P-mediated cell transformation and tumor initiation remain unclear. Here we showed that EGR1 was significantly down-regulated during human bronchial epithelial cell transformation and mice lung carcinogenesis upon B[a]P and its active form BPDE exposure, respectively. In contrast, overexpression of EGR1 inhibited the BPDE-induced cell malignant transformation. Moreover, miR-377-3p was strongly enhanced by BPDE/B[a]P. It was crucial for the inhibition of EGR1 expression by targeting EGR1’s 3'UTR. MiR-377-3p antagomir reversed the effect of EGR1 downregulation in the cell malignant transformation and tumour initiation models. The B[a]P-induced molecular changes were evaluated by immunohistochemistry in clinical lung cancer tissues and examined with clinic database. Furthermore, EGR1 inhibition was also involved in the regulation of Wnt/-catenin transduction, which could promote the lung tumorigenesis following B[a]P/BPDE exposure. Taken together, the results demonstrated that Benzo[a]pyrene exposure may induce lung tumorigenesis through miR-377-3p mediated reduction of EGR1 expression, suggesting an important role of EGR1 in PAH-induced lung carcinogenesis.